Local communities' perception of mangrove ecosystem degradation factors and mitigation measures (Sciences et Technologies pour l’Agriculture Durable, 2026)
Mangroves are ecosystems rich in biodiversity, playing a key role in coastal protection, carbon sequestration, and the preservation of natural habitats. In Benin, they are severely threatened, particularly due to the strong dependence of local populations on their resources. While most existing research focuses on remote sensing and mapping, this study stands out by emphasizing community perceptions of mangrove degradation factors at Ramsar site 1017. Through a semi-structured survey conducted with 306 households across ten coastal villages, socioeconomic, demographic, and perception data were collected. The main factors identified include environmental issues (floods, droughts, strong winds, erosion) and human-induced pressures (wood harvesting, agriculture, fishing), exacerbated by poverty and weak law enforcement. The study distinguishes three types of households: the first, composed mainly of women and the elderly, is engaged in salt production; the second, more educated, focuses on fishing; and the third, primarily made up of young men, combines fishing and farming. Each group perceives the causes and severity of degradation differently, highlighting the need for tailored approaches. Communities propose restoration, conservation, and the sacralization of mangroves as key strategies to combat degradation. The study concludes with an urgent call for the establishment of a clear legislative framework and the development of restoration projects to ensure the sustainable management of these vital ecosystems
Keywords: Spatio-temporal dynamic; Mangroves; Mangrove degradation; Attenuation measures; Household types